OPTIMALISASI DANA ZAKAT BAZNAS KOTA SURABAYA TERHADAP BIAYA PENDIDIKAN UNTUK MENURUNKAN ANGKA PUTUS SEKOLAH DI KOTA SURABAYA - Galang Afiyat Robbani; Ni'matus Sholihah; Mukhlishah AM (JURNAL ILMIAH EDUNOMIKA, 2026)
Zakat, as a socio-economic instrument in Islam, plays a strategic role in improving community welfare, including in education. Through the "Smart Surabaya" program and various forms of scholarships and educational assistance, BAZNAS Surabaya strives to provide equitable and equal access to education for students from underprivileged families. This study aims to analyze how the optimization of zakat funds by the National Zakat Agency (BAZNAS) of Surabaya City contributes to education financing and reduces dropout rates among underprivileged communities. This study uses a qualitative descriptive approach. Data collection methods in this study include observation, interviews, and documentation. The results show that BAZNAS Surabaya manages zakat professionally, transparently, and accountably through a structured collection, distribution, and utilization mechanism. The zakat scholarship program is designed based on an analysis of the recipients' needs and is implemented through a strict selection system, educational mentoring, and periodic evaluation to ensure program effectiveness